Uji Kelayakan Penuntun Praktikum Genetika Berbasis Keterampilan Proses Sains Berdasarkan Ahli Materi dan Ahli Desain - Ivan Lauren; Fauziyah Harahap; Tumiur Gultom (Jurnal Pendidikan Biologi, 2016)
This research was aimed to develop a Genetics Practical Guidance book Based on Science Process Skills which feasible empirically according to content and design expert. This Genetics Practical Guidance book was developed integrated to 11 components of science process skills in each practicum activity. This science process skills allowed students to explore the information in the form of facts and concepts of science. This study was conducted from April 2016 to August 2016. This research and development used Borg and Gall model. However this study was limited to validation from content expert and design expert. Validation to content experts was carried out to assess the feasibility of the contents, feasibility of the presentation, and the feasibility of science process skills components on the product. Validation of design experts carried out to assess the feasibility of the design of cover, cover typography, content design and content illustration on practical guidance book. Data validation was analyzed descriptively qualitative.The result shown that according to conten experts the product has average percentage of 88.2% with very good criteria, where as validation from design expert shown the average percentage of 88.3% with very good criteria. As the conclusion Genetics Practical Guidance book based on Science Process Skills is feasible empirically based on content and design expert to be continue to the next steps.